Structural, Vibrational, Quantum Chemical Calculations, Thermal and Antimicrobial Studies on Sulphate Salt of 3-Nitroaniline - Thangarasu, S.; Siva, V.; Asath Bahadur, S.; Athimoolam, S. (Asian Journal of Chemistry, 2020)
In this work, bis(3-nitroanilinium) sulfate (3NASU) has been synthesized and crystallized successfully by solution growth combined with solvent evaporation technique. The studied salt, 3NASU molecular structure has been optimized with density functional theory (DFT) using B3LYP function and Hartree-Fock method with a 6-311++G(d,p) basis set. The geometrical parameters of 3NASU have been analyzed. The computed vibrational spectra were compared with experimental result which show appreciable agreement. Thermal stability of the crystal was analyzed with TGA/DTA and the melting points of the salt identified at 210 ºC. HOMO-LUMO energy calculations have shown the charge transfer within the molecule. The possible pharmaceutical/biological activity of the salts confirmed by the frontier molecular orbital (FMO) analysis have lower band gap value. The antimicrobial activity of grown crystals were tested against certain potentially threatening microbes.